A study of the level of mathematical moral values among students of the Faculty of Physical Education at Al-Mustansiriya University (Journal of the College of Basic Education, 2023)
The study aimed to study the level of mathematical moral values and the field in which they rise among students of the Faculty of Physical Education, the third stage at Al-Mustansiriya University.In order to achieve the objectives of the research, the researchers intended to build a scale of mathematical moral values, which consisted in its final form of 40 items after deleting the two positions 41_42 for not achieving homogeneity, discrimination and weak correlation in these two positions.The researchers assumed that there is a high level of mathematical moral values, and this level varies according to the fields of the research sample.The researchers used the questionnaire as a means of collecting data, and it was processed by the following statistical means, the arithmetic mean, standard deviation, weight percentile, and the simple correlation coefficient Pearson Ttest_ weight percentile.The researchers concluded that there is a good level of mathematical ethical values.